2017
DOI: 10.1177/0269881117695861
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine disrupts safety learning by enhancing fear associated with a safety cue via the dorsal hippocampus

Abstract: Learned safety, a learning process in which a cue becomes associated with the absence of threat, is disrupted in individuals with post-traumatic stress disorder (PTSD). A bi-directional relationship exists between smoking and PTSD and one potential explanation is that nicotine-associated changes in cognition facilitate PTSD emotional dysregulation by disrupting safety associations. Therefore, we investigated whether nicotine would disrupt learned safety by enhancing fear associated with a safety cue. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 91 publications
(148 reference statements)
3
8
0
Order By: Relevance
“…Our results have several implications for anxiety and stress disorders in humans. In conjunction with the results of our previous studies (e.g., (Connor et al , 2017; Kutlu et al , 2014, 2016a, 2016b; Kutlu and Gould, 2014), the results of the present study strongly suggest that nicotine exposure might be a contributing factor to fundamental maladaptive behaviors such as inability to inhibit and extinguish fear observed in these psychopathologies. In line with this hypothesis, we recently showed that chronic nicotine exposure both in mice and humans is associated with a decreased ability to learn cues signaling safety (Kutlu et al , 2018a).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results have several implications for anxiety and stress disorders in humans. In conjunction with the results of our previous studies (e.g., (Connor et al , 2017; Kutlu et al , 2014, 2016a, 2016b; Kutlu and Gould, 2014), the results of the present study strongly suggest that nicotine exposure might be a contributing factor to fundamental maladaptive behaviors such as inability to inhibit and extinguish fear observed in these psychopathologies. In line with this hypothesis, we recently showed that chronic nicotine exposure both in mice and humans is associated with a decreased ability to learn cues signaling safety (Kutlu et al , 2018a).…”
Section: Discussionsupporting
confidence: 89%
“…However, the effects of nicotine are not limited to enhancing fear memories. Previous studies from our laboratory have demonstrated that nicotine administration impaired fear extinction and safety learning in mice (Connor et al , 2017; Kutlu et al , 2014, 2016a, 2017a, 2017b, 2018a; Kutlu and Gould, 2014). Specifically, acute nicotine administration was shown to cause deficits in encoding, consolidation, and retrieval of contextual fear extinction memories (Kutlu et al , 2016a, 2016b; Kutlu and Gould, 2014; Oliver et al , 2018), as well as deficits in contextual safety discrimination (Kutlu and Gould, 2014).…”
mentioning
confidence: 88%
“…Specifically, we arranged a brief (10 s) auditory CS to either precede (forward conditioning, FW) or follow (backward conditioning, BW) a footshock US in rats. Although extensively-trained BW CSs become conditioned inhibitors that dampen responding to other first-order excitatory cues (Andreatta et al, 2012; Ayres et al, 1976; Christianson et al, 2011; Gerber et al, 2014; Moscovitch and LoLordo, 1968; Siegel and Domjan, 1971), minimally-trained BW CSs elicit excitatory conditioned responses that transfer across contexts (Ayres et al, 1987; Barnet and Miller, 1996; Bevins and Ayres, 1992; Chang et al, 2003; Connor et al, 2017; Heth, 1976; Mahoney and Ayres, 1976; Prével et al, 2018; Prével et al, 2016; Rescorla, 1968). After conditioning, we examined the effect of pharmacological inactivation of the BNST on freezing to FW or BW CSs.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that nicotine caused extended fear responses, enhanced fear conditioning ( 22 ), delayed extinction of fear memories ( 23 , 24 ), and disrupted safety learning ( 17 , 25 ). In humans, children exposed to SHCS had higher rates of major depressive disorder and attention-deficit/hyperactivity disorder ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in laboratory rodents show that nicotine is a causal agent of extended fear response. In mice, nicotine enhanced fear conditioning ( 22 ), delayed extinction of fear memories ( 23 , 24 ), and disrupted safety learning ( 17 , 25 ). While not directly tested, these effects of nicotine on fear learning and extinction could be related to altered hypothalamic-pituitary-adrenal function in those exposed to second hand smoke as well as active smokers.…”
Section: Introductionmentioning
confidence: 99%